2003
DOI: 10.1002/ijc.11149
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant E. coli efficiently delivers antigen and maturation signals to human dendritic cells: Presentation of MART1 to CD8+ T cells

Abstract: The generation of tumour-specific cytotoxic T-lymphocyte (CTL) responses is the primary focus in the design of immunotherapeutic cancer vaccines. We have recently demonstrated generation of ovalbumin (OVA)-specific CTLs and tumour-protection in a murine tumour model using vaccination with dendritic cells (DCs) pulsed with E. coli expressing listeriolysin O (LLO) and OVA as a model antigen. In this system paraformaldehyde fixation of E. coli/LLO provided an additional safety feature without compromising vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
(100 reference statements)
0
18
1
Order By: Relevance
“…Using the model tumor Ag OVA, we have demonstrated that E. coli LLO OVA is a powerful tool for successful antitumor vaccination, through its ability to generate high-avidity CTL and Treg functional defect leading to the rejection of tumor. Recombinant E. coli have already been described as protein delivery vectors for professional phagocytic cells (6,20,21) and presentation of the OVA epitope on MHC class I by E. coli LLO/OVA has been shown to be orders of magnitude more efficient than E. coli OVA strains (6,20). Therefore, the difference in efficacy of the two vaccines may be attributed to a difference in efficiency of MHC class I presentation on APCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the model tumor Ag OVA, we have demonstrated that E. coli LLO OVA is a powerful tool for successful antitumor vaccination, through its ability to generate high-avidity CTL and Treg functional defect leading to the rejection of tumor. Recombinant E. coli have already been described as protein delivery vectors for professional phagocytic cells (6,20,21) and presentation of the OVA epitope on MHC class I by E. coli LLO/OVA has been shown to be orders of magnitude more efficient than E. coli OVA strains (6,20). Therefore, the difference in efficacy of the two vaccines may be attributed to a difference in efficiency of MHC class I presentation on APCs.…”
Section: Discussionmentioning
confidence: 99%
“…Through the pore-forming action of LLO, the cytoplasmic contents of the bacteria can then escape into the cytosol and thereby be processed by the proteasome. In vitro, this LLO-mediated process has been shown to improve MHC class I presentation of the OVA H2-K b -restricted epitope SIINFEKL by mouse macrophages (20), mouse bone-marrow-derived dendritic cells (BMDCs) (6), the HLA-A2-restricted MART1 [27][28][29][30][31][32][33][34][35] epitope (21), and the immunodominant epitope of the influenza matrix protein (22) by human monocytes-derived DCs. In vivo, s.c. injection of E. coli LLO expressing the model chicken OVA Ag (E. coli LLO/OVA) has been shown to trigger a very strong antitumor response against the highly aggressive B16/ OVA melanoma cell line (6) (B16-OVA).…”
mentioning
confidence: 99%
“…28 E. coli coexpressing LLO and a model antigen (truncated chicken ovalbumin, OVA) were incubated with the cells, taken up and presentation of the OVA epitope on MHC class I was observed. 26,27 In addition, an antitumour effect was observed when these bacteria were used in a vaccination protocol.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similar in vitro data were obtained when human DCs were used to present MART-1 antigen epitopes. 28 In the present communication, we have used an invasive E. coli to deliver therapeutically relevant molecules to mouse and human nonprofessional phagocytic cells. We demonstrate that protein delivery is much more efficient than gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of a typical human melanoma antigen (MART1) instead of OVA in the vaccine efficiently delivered the MART127-35 antigen epitope for processing and presentation by human MoDCs. 117 The anti-tumor efficacy of the paraformaldehydefixed E. coli vaccine is maintained, and this vaccine is significantly less harmful to humans. Similarly, another research team illustrated that an LLO-based E. coli vaccine could induce a strong immune response against a WT1-expressing leukemia tumor in vivo through enhanced CTL activity.…”
Section: Llo-based Immunotoxin/immunoliposome For Killing Tumor Cellsmentioning
confidence: 99%